CLINICAL EFFECTIVENESS OF HIGH-DOSE IMMUNOSUPPRESSIVE THERAPY WITH AUTOLOGOUS HEMATOPOIETIC STEM CELL TRANSPLANTATION IN MULTIPLE SCLEROSIS PATIENTS - D. A. Fedorenko; V. Ya. Melnichenko; T. I. Ionova; E. B. Yaroshenko (Вестник трансплантологии и искусственных органов, 2014)
Multiple sclerosis (MS) is a major infl ammatory and demyelinating disease of the central nervous system (CNS), associated with a broad spectrum of physical, psychological, and social impairments. High-dose immunosuppressive therapy (HDIT) with autologous hematopoietic stem cell transplantation (AHSCT) is a new and promising approach to MS treatment. In this paper we present the clinical monitoring results of 93 patients with different MS types after AHSCT. The mobilization and transplantation procedures were well tolerated. At long-termfollow-up (mean 47,2 months), the overall clinical response in terms of disease improvement or stabilization was 95% in patients with relapsing-remitting MS and 77,5% in patients with progressive MS. The results of our study support the feasibility of AHSCT in MS patients.